Specification of nabu and nuts functioning in the system of specialized anti-corruption bodies of ukraine - Prokopiv, Bohdan (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article outlines the peculiarities of the functioning of some specialized anti-corruption bodies of Ukraine : the National Anti-Corruption Bureau (NABU) and the National Agency for the Prevention of Corruption (NAPC). There are investigated the specifics of their activity and carried out a practical comparative analysis of the purposes of their creation and performed functions